UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) PADA TEMA PERKEMBANGAN TEKNOLOGI DI KELAS III SDN 066050 MEDAN DENAI - Debora Ayu Nengsih Panjaitan; Ester Julinda Simarmata; Anton Sitepu; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to improve students’ learning outcomes by using the Think Talk Write (TTW) model on the theme of technology development at grade III of SDN 066050 Medan Denai in the academic year of 2020/2021. This study utilized a Classroom Action Research (CAR) design. The subjects in this study were the third-grade students of SDN 066050 Medan Denai. The study results showed that students’ learning outcomes on the theme of technological development increased, especially for the sub-theme of food production technology development 1 and 2, at grade III of SDN 066050 Medan Denai in the academic year of 2020/2021. In the first cycle, eight students (34.78%) reached the target scores while 15 students (65,22%) did not reach the target scores, with an average score of 65,43. In the second cycle, 19 students (82,60%) reached the target score while four students (17,40%) did not reach the target score, with an average score of 81,56. The learning outcomes increased after revising the action in cycle II. Then, the action was stopped in cycle II because it had reached the success criteria. In conclusion, the TTW learning model increased the students’ learning outcomes in the theme of technological development at grade III of SDN 066050 Medan Denai